Flat-Panel-Rectenna With Broad RF Energy Harvesting Coverage for Wireless-Powered Sensor Applications - Yan Han; Eunji Kim; Han Lim Lee (IEEE Access)
To circumvent the issue of significant space occupation associated with omnidirectional antenna-based rectennas and to seamlessly integrate into self-powered applications with minimal uncovered zones, this paper presents a new flat-panel rectenna (FPR) designed specifically for microwave-based wireless power charged sensor applications. This innovation aims to optimize space efficiency and enhance energy capture capabilities, providing a more effective solution for the continuous and reliable operation of wireless powered devices in various sectors. The proposed compact rectenna is designed with a planar antenna featuring wide beamwidth and an RF-to-DC conversion network that includes a dual-voltage rectifier architecture and a customized matching network to optimize RF-to-DC conversion efficiency. The FPR is then integrated with a batteryless heart rate sensor, enabling the sensor to operate and expand its physical orientation while maintaining accurate monitoring. The performance of the proposed RF energy harvester was evaluated at 5.8 GHz, showing a half-power coverage of 144.6° with respect to a peak antenna gain of 3.34 dBi, and a peak RF-to-DC conversion efficiency of 51.8%. Additionally, the batteryless sensor was shown to function effectively with a maximum RF energy incident angle of 140°, despite the flat-panel architecture.